2013
DOI: 10.1002/chem.201203517
|View full text |Cite
|
Sign up to set email alerts
|

Diels–Alder and Retro‐Diels–Alder Cycloadditions of (1,2,3,4,5‐Pentamethyl)cyclopentadiene to La@C2v‐C82: Regioselectivity and Product Stability

Abstract: One of the most important reactions in fullerene chemistry is the Diels-Alder (DA) reaction. In two previous experimental studies, the DA cycloaddition reactions of cyclopentadiene (Cp) and 1,2,3,4,5-pentamethylcyclopentadiene (Cp*) with La@C(2v)-C(82) were investigated. The attack of Cp was proposed to occur on bond 19, whereas that of Cp* was confirmed by X-ray analysis to be over bond o. Moreover, the stabilities of the Cp and Cp* adducts were found to be significantly different, that is, the decomposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 112 publications
1
25
0
Order By: Relevance
“…Endohedral fullerenes containing interstitial metal atoms have attracted particular interest owing to their novel properties with potential applications in biomedicine and photovoltaics among others issues. The interstitial metal atoms modify the behavior of the external carbon cage, thereby resulting in a different chemical reactivity compared to the corresponding hollow cage . Endohedral metallofullerenes (EMF) can encapsulate actinide metals, including uranium and thorium, leading to molecular materials displaying fullerene stability as well as the chemistry of the interstitial actinide atom.…”
Section: Introductionmentioning
confidence: 99%
“…Endohedral fullerenes containing interstitial metal atoms have attracted particular interest owing to their novel properties with potential applications in biomedicine and photovoltaics among others issues. The interstitial metal atoms modify the behavior of the external carbon cage, thereby resulting in a different chemical reactivity compared to the corresponding hollow cage . Endohedral metallofullerenes (EMF) can encapsulate actinide metals, including uranium and thorium, leading to molecular materials displaying fullerene stability as well as the chemistry of the interstitial actinide atom.…”
Section: Introductionmentioning
confidence: 99%
“…One important reaction applied to the chemical functionalization of fullerenes is Diels–Alder cycloaddition reaction . Previous studies have uncovered an interesting finding that fullerenes encapsulated with additional atoms, ions, or clusters, which are known as endohedral metallofullerenes (EMFs), greatly alter the rate of Diels–Alder reaction . The effect of the encapsulation on the reactivity of fullerenes is further clearly shown in a recent study by Kawakami et al who found that [Li + @C 60 ] ( PF6) experiences a much higher reactivity for Diels–Alder cycloaddition toward cyclopentadiene (CpH) in comparison to that of empty C 60 …”
Section: Introductionmentioning
confidence: 98%
“…The La@C 2v -C 82 EMF,w hich in the case of Ce@C 2v -C 82 is approximately four times more abundant than the analogous C s -C 82 , [17] has been the subjecto fm any studies. [18][19][20] For example,t he first EMF functionalization was achieved for La@C 2v -C 82 throughaphotochemical reaction with disilirane. [21] The electronic and structural properties of the La@C 2v -C 82 cage have been studied already.A ccordingt othe ionic model, [22][23][24][25] charget ransfer from the La atom to the fullerene cage occurs, and as ar esult, the formal electronic structure of La@C 2v -C 82 is describeda sL a 3 + @C 2v -C 82 3À ,w ithan umber of unpairedelectrons located on the fullerene cage.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical functionalization of EMFs [5,6] is commonly achieved through cycloaddition reactions, the most important being: Diels-Alder, [18,29] 1,3-dipolar (or Prato), [30] and nucleophilic [2+ +1] Bingel-Hirsch (BH) additions. [31][32][33] The BH addition is acyclopropanation reaction in which af ullerenea nd diethyl bromomalonate react in the presence of as trong base such as 1,8-diazabicycloundec-7-ene (DBU) or sodium hydride to produce am ethanofullerene or af ulleroid.…”
Section: Introductionmentioning
confidence: 99%